Cooling Protocols Impact on Nickel-Titanium Rotary Instruments Cyclic Fatigue Resistance Under Extreme Curvatures and Sodium Hypochlorite - Ranparia, Palak Ravjibhai; Joshi, Chintan; Somani, Mona; Patel, Aashray; Desai, Urooj; Prajapati, Janki (UI Scholars Hub, 2025)
Objective: In this work, Hyflex CM, TruNatomy, and Plex V heat-treated nickel titanium rotary instruments were evaluated at body temperature (36 °C ± 1 °C) with and without a cooling protocol to assess the cyclic fatigue resistance. Methods: A 90° curved stainless-steel block was used for cyclic fatigue tests on 60 randomly selected rotary instruments, divided into two groups of 30: body temperature (n = 10) and body temperature with cooling (n = 10). Instruments were further subdivided into 6 groups of 3 different instruments. Cooling protocol group instruments received 5-second spray cooling every 30 seconds, along with continuous 5% sodium hypochlorite. Instrument fractures were recorded via audiovisual methods, inspected under a stereomicroscope, and statistically analyzed. Results: Significant cyclic fatigue resistance was observed in both body temperature and cooling protocol groups in intergroup and intragroup comparisons. Plex V files outperformed others at body temperature, while TruNatomy showed superior cyclic fatigue resistance in the cooling protocol group. Each group displayed expected signs of cyclic fatigue behavior under the stereomicroscope. Conclusion: All three instruments showed comparable cyclic fatigue resistance at body temperature, and the cooling treatment enhanced their resistance. TruNatomy presents a better outcome than other tested files after the cooling protocol.